Chemical Composition and Antimicrobial Activity of Teucrium Capitatum L. Subsp. Lusitanicum (Schreb.) T. Navarro & Rosua Essential Oil. (24th November 2020) - Debbabi, Haïfa; El Mokni, Ridha; Jlassi, Ibrahim; Joshi, Rajesh K; Hammami, Saoussen
Abstract: Chemical composition and antimicrobial activity of Teucrium capitatum L. subsp . lusitanicum essential oil was investigated for the first time in the present study. Qualitative and quantitative analyses of the chemical composition by gas chromatography and mass spectrometry (GC–FID and GC–MS) revealed the presence of 60 compounds representing 97.6% of the whole constituents. The main compounds were germacrene D (47.1%), spathulenol (5.8%), α -selinene (5.3%), germacrene A (2.9%), δ -cadinene (2.8%) and cubenol (2.7%). In vitro, the antimicrobial activity was investigated against five bacterial strains along with the yeast Candida albicans using broth microdilution assay. T. capitatum subsp. lusitanicum essential oil showed significant activity against the gram-positive bacteria Staphylococcus aureus (MIC = MBC = 78 μg mL −1 ), Bacillus subtilis (MIC = MBC = 156 μg mL −1 ) and the yeast C. albicans (MIC = MFC = 156 μg mL −1 ). The great potential of antimicrobial effects is most likely due to the very high percentage of sesquiterpene hydrocarbons particularly to germacrene D, for which the antimicrobial properties have been previously reported.